Preliminary Monetary Values for the Reliability of Travel Times in Freight Transport - Jong, Gerard de; Kouwenhoven, Marco; Kroes, Eric; Rietveld, Piet; Warffemius, Pim (European Journal of Transport and Infrastructure Research, 2009)
In The Netherlands, major infrastructure projects are assessed using cost-benefit analysis, following official guidelines. Until recently, the reliability of travel times could not be included in the cost-benefit analysis, because the corresponding monetary valuation was unknown. In recent years, the literature on valuing reliability of travel times was reviewed for the Dutch transport ministry. The outcomes of this were discussed at an expert workshop, which led to an agreement on preliminary monetary values for passenger transport. A key concept is that of the reliability ratio. This is defined as the value of reliability (measured as the standard deviation of travel time) divided by the value of travel time itself. For freight transport a follow-up study was carried out, which transforms the results of earlier stated preference research into a reliability ratio. The paper presents and explains the preliminary values, focussing on the derivation of reliability values for freight transport. It also describes how these values can be used in practical project evaluations.